CONCEPTUAL MODEL FOR EVALUATING THE EFFECTIVENESS OF PPP PROJECTS - Lina Alexandrovna Mazharova (Science and Innovation Center Publishing House, 2020)
The article presents the author’s model for evaluating the effectiveness of PPP projects by government agencies.